Strategic aspects of improving the marketing support of the promotion of innovative products of construction enterprises - Ivakhnenko , I.S (Ways to Improve Construction Efficiency, 2022)
This work substantiates the essence of the process of marketing promotion of an innovative product, the development of practical measures aimed at improving the toolkit of marketing support for the promotion of an innovative product by construction enterprises. In the range of key elements of the innovative activity of the enterprise, one should not forget about the importance of marketing, because it is marketing that is often considered a panacea for all problems. The state of the company's external environment is rather unstable, which is affected by completely new conditions for the development of market relations, globalization and internationalization, and crisis phenomena in the economy. A number of the listed factors force the enterprise to analyze its internal capabilities and adapt to the requirements dictated by the market. The active involvement of effective marketing measures will solve this kind of problem, and a successfully created innovative product needs marketing promotion to the construction market. Adaptation to the conditions of operation on domestic and international markets forces enterprises to be flexible and skillfully adapt to the dynamics of changes. Therefore, it is important to focus on innovative activity, which includes the creation, distribution and use of innovative products. In order to achieve sustainable commercial success, enterprises need to create products or services that can attract the attention of consumers, despite the existence of their analogues on the market. Thanks to innovations, you can increase your business income and take a leading place among competitors Marketing support for the promotion of an innovative product by construction enterprises on the market is a set of actions aimed at communicating with the target audience to encourage them to buy, which contribute to the sale of the product on the market. It is important for the buyer to see the product in its various presentations. Therefore, it is worth considering marketing promotion as a set of tools. Each enterprise separates for itself a set of measures aimed at product promotion. The promotion structure is not about one thing, it is a combination of different types of promotion (radio advertising, personal selling, creating your own website, article in a print publication, developing a page on a social network) - it is a single system. Thus, it was established that in order for an innovative product produced by an enterprise to reach specific consumers, an effective set of marketing measures is necessary for its promotion, therefore, the application of innovation marketing is successful. Innovation marketing as a type of activity is related to the development and market promotion of new products, equipment, services, and the latest technologies.